Discourses of power and the politics of representation of the COVID-19 pandemic - Anabela da Conceição Pereira (Theory and Event, 2026)
This essay discusses the visuality of the COVID-19 pandemic. The central argument is that absence and presence have strongly epitomized the media’s representation of the virus, as shown on social media, television, and street advertisements. The boundaries between the two concepts were explored through the system of representations of the virus, serving as a guiding principle for the pandemic’s changing course, simultaneously by individuals, artists, political discourses, and the media. These images capture the space where the aesthetics and politics of the virus intersected as sanitary measures were being implemented and social distancing and seclusion were mandatory. Discourses of power based on hygiene, bodies, and virus control, as well as a novel form of social life, were established, and all became part of its visual dimension.